Lung ultrasound score and diaphragm ultrasound in weaning from mechanical ventilation: are they different in patients with and without COVID-19? - Laura Cordeiro Madeira; Paulo de Tarso Dalcin; Gabriele Heinen Schuster; Bruna Conte; Jonas Michel Wolf; Annia Schreiber; Jean-Jacques Rouby; Felippe Leopoldo Dexheimer-Neto (Jornal Brasileiro de Pneumologia)
ABSTRACT Objective: To compare pre-extubation physiological characteristics and ultrasound variables between patients intubated for COVID-19 compared to a clinical population and those intubated for other reasons. Methods: This was a secondary analysis of a prospective cohort study of patients undergoing invasive mechanical ventilation (IMV) for more than 48 h. Patients were divided into two groups: those intubated for COVID-19-induced ARDS and those intubated for other clinical reasons. Ultrasound assessment of lung and diaphragm function was performed before extubation. The results were compared between the two groups of patients. Results: In comparison with the patients without COVID-19, those with the disease were younger (a median age of 58 [46-76] years vs. a median age of 75 [69-85] years; p = 0.01), had fewer comorbidities (a median Charlson Comorbidity Index of 2 [1-4] vs. a median Charlson Comorbidity Index of 5 [4-6]; p < 0.01), and were less severely ill at admission (a median APACHE II score of 9 [8-14] vs. a median APACHE II score of 18 [13-22]; p < 0.01). In addition, the median duration of IMV was longer in the COVID-19 patients (11 [9-23] days vs. 6 [3-8] days; p < 0.01). Although extubation success rates were similar between the COVID-19 and non-COVID-19 groups (22 [71%] vs. 35 [77.8%]), median lung ultrasound score differed between the two groups (23 [18-25] vs. 15 [11-18]; p < 0.01), as did median diaphragmatic excursion (2.1 [1.7-2.4] vs. 1.7 [1.2-2.0]; p < 0.01). Conclusions: Although patients with COVID-19 requiring ventilatory support are younger and have fewer comorbidities than those intubated for other clinical reasons, they experience longer hospital stays. Although lung ultrasound score can differ between patients with and without COVID-19, these differences do not significantly translate into extubation success rates. Therefore, the utility of ultrasound scores in weaning COVID-19 patients from IMV needs further study.